Notoginsenoside R1 Reverses Abnormal Autophagy in Hippocampal Neurons of Mice With Sleep Deprivation Through Melatonin Receptor 1A - Cao, Yin; Li, Qinglin; Zhou, An; Ke, Zunji; Chen, Shengqi; Li, Mingrui; Gong, Zipeng; Wang, Zhengtao; Wu, Xiaojun (Frontiers in Pharmacology, 2021)
Sleep deprivation (SD) may cause serious neural injury in central nervous system, leading to impairment of learning and memory. Melatonin receptor 1A (MTNR1A) plays an important role in the sleep regulation upon activation by melatonin. The present study was to investigate if notoginsenoside R1 (NGR1), an active compound isolated from Panax notoginseng, could alleviate neural injury, thus improve the impaired learning and memory of SD mice, as well as to explore its underlying action mechanism through modulating MTNR1A. Our results showed that NGR1 administration improved the impaired learning and memory of SD mice. NGR1 prevented the morphological damage and the accumulation of autophagosomes in hippocampus of SD mice. At molecular level, NGR1 reversed the expressions of proteins involved in autophagy and apoptosis, such as Beclin-1, LC3B, p62, Bcl-2, Bax and cleaved-caspase 3. Furthermore, the effect of NGR1 was found to be closely related with MTNR1A mediated PI3K/Akt/mTOR signaling pathway. On HT-22 cells induced by autophagy inducer rapamycin NGR1 markedly attenuated the excessive autophagy and apoptosis, and the alleviative effect was abolished by MTNR1A inhibitor. Taken together, NGR1 was shown to alleviate the impaired learning and memory of SD mice, and its function might be exerted through reduction of excessive autophagy and apoptosis of hippocampal neurons by regulating MTNR1A mediated PI3K/Akt/mTOR signaling pathway.